Two new species of Kalopona (Hemiptera: Cicadellidae: Gyponini) from Brazil - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2017)
Kalopona is a small genus with five species distributed in Brazil, Colombia and Mexico. Two new Brazilian species of Kalopona Freytag, 2015 are described and illustrated: K. insigna sp. nov., from Amazonas and K. sagytta sp. nov., from Mato Grosso. A key to the seven known species of Kalopona is presented.